Creating a Patient-Based Diagnostic Checklist for Functional Tics During the COVID-19 Pandemic. Issue 5 (October 2022) - Trau, Steven Patrick; Quehl, Luke; Tsujimoto, Tamy H. M.; Lin, Feng-Chang; Singer, Harvey S.
Abstract : Background and Objectives: Since the onset of the COVID-19 pandemic, there has been a dramatic change in the presentation of patients with tics. The explosive presentation of atypical tics (TT) has been noted worldwide and thought to be the manifestation of a pandemic-associated functional neurologic disorder following social media exposure to tics. Nevertheless, despite the frequent diagnosis of functional tics (FT), there are no existing formal diagnostic criteria. The primary aim of this study was to create a patient-based diagnostic checklist for making the diagnosis of a functional tic disorder (FTD) during the COVID-19 pandemic. Methods: A retrospective chart review at a single institution during the pandemic was performed. Based on the available literature, diagnostic criteria were created for TT, FT, and patients with dramatically evolving symptoms (i.e., mixed with prior history of mild tics with later fulminant functional worsening). Patient demographics, comorbidities, and tic characteristics of these groups were then compared. Following initial assessments, new diagnostic criteria were established and statistically reanalyzed. Results: One hundred ninety-eight patients underwent investigation. Significant differences in age, sex, psychological comorbidities, tic characteristics, and tic severity were found between patients with TT when compared with either of the 2 the functional groups. Only the presence of rostrocaudal progression and increased obsessive-compulsive behaviors were significantly different between patients with new-onset FT and those with functional worsening of a previous tic disorder. Results also showed that age at tic onset was not a contributing factor for group differentiation. Many patients with FT were not exposed to videos depicting tics on social media. Discussion: This study confirms the presence of a distinct presentation of aTT during the pandemic period. It further establishes the validity of specific criteria useful in dividing patients with tics into 3 formal diagnostic criteria: (1) primary tic disorders (PTDs), (2) a strictly FTD, and (3) a mixed tic disorder consisting of patients with an initial history of a PTD and the later development of FT. Explicit diagnostic criteria should enable clinicians and researchers to make a definitive identification and assist patients and families become more knowledgeable and accepting of the diagnosis of FT.